2019
DOI: 10.2174/1381612825666190701150803
|View full text |Cite
|
Sign up to set email alerts
|

Piperine: Old Spice and New Nutraceutical?

Abstract: Background: Many of the activities associated with pepper fruits have been attributed to piperine, the most active compound present in these spices. Objective: This paper aims to provide an overview of the known properties of piperine, i.e. piperine’s chemistry, its physiological activity, documented interactions as a bioenhancer and reported data concerning its toxicity, antioxidant properties and anticancer activity. Discussion: It is known that piperine possesses several properties. In its interaction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 122 publications
0
30
0
1
Order By: Relevance
“…Over the last twenty years, numerous studies have shown that many natural products display chemoprotective properties against different types of cancers [1,2]. In this context, piperine (a trans-trans isomer of 1-piperoyl piperidine) (Figure 1), the pungent amide present in Piper spices, such as the widely used black pepper (Piper nigrum L.,) is known to present a broad spectrum of biological activities, including its anti-cancer effect [3][4][5]. Regarding the multidrug resistance (MDR) phenotype, a serious obstacle for the treatment of cancer patients [6], previous studies have demonstrated that piperine inhibits the activity of the main ABC transporters related to MDR phenotype [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last twenty years, numerous studies have shown that many natural products display chemoprotective properties against different types of cancers [1,2]. In this context, piperine (a trans-trans isomer of 1-piperoyl piperidine) (Figure 1), the pungent amide present in Piper spices, such as the widely used black pepper (Piper nigrum L.,) is known to present a broad spectrum of biological activities, including its anti-cancer effect [3][4][5]. Regarding the multidrug resistance (MDR) phenotype, a serious obstacle for the treatment of cancer patients [6], previous studies have demonstrated that piperine inhibits the activity of the main ABC transporters related to MDR phenotype [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we examined the TLR-4, CD11c and IL-1βwith a Western blot analysis. The results showed that piperine (20,40, and 80 µM) inhibited the expression of TLR-4, IL-1β, and CD11c in the RAW264.7 cells after LPS treatment (Fig. 10A-B).…”
Section: Effect Of Piperine On In Vitro Macrophage Polarizationmentioning
confidence: 89%
“…Piperine is the major alkaloid presented in black pepper (Piper nigrum), long pepper (Piper longum), and many other piper species. Piperine exhibits a wide range of biological properties, such as immunomodulatory, anti-oxidant, anti-lipid metabolism disorder, and anti-inflammatory [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Piperine (1, Figure 1) is a well-known natural product that is derived from peppercorns [1][2][3]. Many biological studies of 1 have been carried out, and these studies have led to a diverse array of biological activities being claimed for this compound [4][5][6][7][8][9]. For example, 1 is reported to exhibit inhibitory activity towards both acetylcholinesterase (AChE) and β-secretase (BACE-1), which suggests that 1 could hold promise as a dual mechanism-of-action treatment for Alzheimer's disease [4,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%